2021
DOI: 10.9734/jpri/2021/v33i26a31469
|View full text |Cite
|
Sign up to set email alerts
|

Study of Malondialdehyde Level and Glutathione Peroxidase Activity in Patients Suffering from Malaria

Abstract: Introduction: Malaria is one of the most common Parasitic infection prevalent worldwide especially in India, South Asia and Africa. About 250 million cases and approximately One million deaths of malaria reported per year worldwide. Oxidative stress (O.S.) has been implicated as possible mediator of thrombocytopenia in malarial patients. All eukaryotic cells, specially immune effector cells generate reactive oxygen species (ROS) and reactive nitrogen species (RNS) as a mean to combat invading microbes i.e. via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Lipid peroxidation indicated by the increased levels of MDA, a biomarker of oxidative stress, is greatly elevated in untreated P. berghei infected mice 32 . Elevated MDA levels in Plasmodium infection has been confirmed by other researchers 34,35 . The increased amount of MDA generated during malaria infection may be caused by activation of the immune system 33 .…”
Section: Resultssupporting
confidence: 62%
“…Lipid peroxidation indicated by the increased levels of MDA, a biomarker of oxidative stress, is greatly elevated in untreated P. berghei infected mice 32 . Elevated MDA levels in Plasmodium infection has been confirmed by other researchers 34,35 . The increased amount of MDA generated during malaria infection may be caused by activation of the immune system 33 .…”
Section: Resultssupporting
confidence: 62%
“…The risk of bias among the included studies was examined using the JBI critical appraisal tools for case–control, cohort, cross-sectional, and experimental studies. The results of the assessment showed that one case–control study lacked exposure period of interest 30 ; four cross-sectional studies lacked the identification and strategy to deal with confounding factors 19 , 21 , 32 , 40 ; and the cohort study had unclear follow-up details 34 . All studies were included in the review (Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies compared blood levels of GPx between malaria patients with P. vivax and P. falciparum infections 37 , 38 , 40 . The findings of the three studies showed similar GPx levels among patients with P. falciparum and P. vivax malaria 37 , 38 , 40 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations